Crocus heuffelianus (Iridaceae), a new record for the Italian flora - Peruzzi, Lorenzo (Phytotaxa, 2016)
The genus Crocus Linnaeus (1753: 36) consists currently of about 200 recognized species occurring from western Europe and northwestern Africa to western China, with the center of species diversity in the Balkan Peninsula and in Turkey (Mathew 1982, Harpke et al. 2016). In the most recent comprehensive classification (Mathew 1982), which relied only on morphology, the genus is divided into two subgenera, the monotypic subgenus Crociris Mathew (1982: 116) and subgenus Crocus. The latter is divided into two sections, i.e. section Crocus and section Nudiscapus Mathew (1982: 61), and includes 15 series (section Crocus: six series; section Nudiscapus: nine series).